Therapeutic hypothermia decreases phenytoin elimination in children with traumatic brain injury - Empey, Philip E; Velez de Mendizabal, Nieves; Bell, Michael J; Bies, Robert R; Anderson, Kacey B; Kochanek, Patrick M; Adelson, P David; Poloyac, Samuel M (Critical care medicine, 2013)
Preclinical and clinical studies have suggested that therapeutic hypothermia, while decreasing neurologic injury, may also lead to drug toxicity that may limit its benefit. Cooling decreases cytochrome P450 (CYP)-mediated drug metabolism, and limited clinical data suggest that drug levels are elevated. Fosphenytoin is metabolized by cytochrome P450 2C, has a narrow therapeutic range, and is a commonly used antiepileptic medication. The objective of this study was to evaluate the impact of therapeutic hypothermia on phenytoin levels and pharmacokinetics in children with severe traumatic brain injury. Pharmacokinetic analysis of subjects participating in a multicenter randomized phase III study of therapeutic hypothermia for severe traumatic brain injury. ICU at the Children's Hospital of Pittsburgh. Nineteen children with severe traumatic brain injury. None. A sum of 121 total and 114 free phenytoin levels were evaluated retrospectively in 10 hypothermia-treated and nine normothermia-treated children who were randomized to 48 hours of cooling to 32-33°C followed by slow rewarming or controlled normothermia. Drug dosing, body temperatures, and demographics were collected during cooling, rewarming, and posttreatment periods (8 d). A trend toward elevated free phenytoin levels in the hypothermia group (p=0.051) to a median of 2.2 mg/L during rewarming was observed and was not explained by dosing differences. Nonlinear mixed-effects modeling incorporating both free and total levels demonstrated that therapeutic hypothermia specifically decreased the time-variant component of the maximum velocity of phenytoin metabolism (Vmax) 4.6-fold (11.6-2.53 mg/hr) and reduced the overall Vmax by ~50%. Simulations showed that the increased risk for drug toxicity extends many days beyond the end of the cooling period. Therapeutic hypothermia significantly reduces phenytoin elimination in children with severe traumatic brain injury leading to increased drug levels for an extended period of time after cooling. Pharmacokinetic interactions between hypothermia and medications should be considered when caring for children receiving this therapy.